Operation land transfer a policy appraisal - Ma. Aurora Carbonell-Catilo (1984)
The policy of government on land redistribution is embodied in Operation Land Transfer (OLT). Substantive and procedural policies circumscribe the effectiveness of OLT. Substantive policies on coverage, landowner compensation and support systems tend to favor the landowning class. Moreover, these policies promote a power structure based on tenurial arrangements. Internal inequalities among the peasantry emerge. Procedural policies are ambiguous and inconsistent, making OLT implementation difficult. A reverse land reform is effected. The recommended policy directions focus on the need to promulgate a code of agrarian reform, incorporate commercial crop land in the OLT coverage, adopt a proportional compensation scheme, mobilize the participation of farmers and farmer-organizations in OLT, and adopt measures to promote the well-being of landless agricultural workers. Alternative forms of property ownership such as the concept of stewardship are suggested for in-dept study.
Keywords: Land reform; Land title registration and transfer; Rural development